2018
DOI: 10.1039/c8cc00271a
|View full text |Cite
|
Sign up to set email alerts
|

Decarbonylative thioetherification by nickel catalysis using air- and moisture-stable nickel precatalysts

Abstract: A general, highly selective method for decarbonylative thioetherification of aryl thioesters by C-S cleavage is reported. These reactions are promoted by a commercially-available, user-friendly, inexpensive, air- and moisture-stable nickel precatalyst. The process occurs with broad functional group tolerance, including free anilines, cyanides, ketones, halides and aryl esters, to efficiently generate thioethers using ubiquitous carboxylic acids as ultimate cross-coupling precursors (cf. conventional aryl halid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(45 citation statements)
references
References 61 publications
0
45
0
Order By: Relevance
“…To design a viable catalytic system, Ni/Ir based metallaphotoredox catalytic system was deemed particularly attractive. The high proficiency of Ni 0 species to undergo oxidative addition and the recent advances in C−H activation mediated by the catalytic generation of a chlorine atom under photocatalytic conditions were both considered suitable due to the high bond dissociation free energy of H−Cl (97 kcal mol −1 ) exceeding those of simple alkanes (91 kcal mol −1 for cyclohexane) . After assessing a variety of organic and transition‐metal photosensitizers, ubiquitous iridium phenylpyridine based photocatalyst Ir[dF(CF 3 )ppy] 2 (dtbbpy)PF 6 was found to be solely effective (Table S1 in the Supporting Information) .…”
Section: Resultsmentioning
confidence: 99%
“…To design a viable catalytic system, Ni/Ir based metallaphotoredox catalytic system was deemed particularly attractive. The high proficiency of Ni 0 species to undergo oxidative addition and the recent advances in C−H activation mediated by the catalytic generation of a chlorine atom under photocatalytic conditions were both considered suitable due to the high bond dissociation free energy of H−Cl (97 kcal mol −1 ) exceeding those of simple alkanes (91 kcal mol −1 for cyclohexane) . After assessing a variety of organic and transition‐metal photosensitizers, ubiquitous iridium phenylpyridine based photocatalyst Ir[dF(CF 3 )ppy] 2 (dtbbpy)PF 6 was found to be solely effective (Table S1 in the Supporting Information) .…”
Section: Resultsmentioning
confidence: 99%
“…Significant effort has also been devoted to the transition‐metal‐catalyzed decarbonylative intramolecular couplings of ketones, esters, and other carboxylic acid derivatives to form C−C and C‐heteroatom bonds [34–49] . Herein, we report our findings on an alternate synthetic route to diaryl selenides via the nickel‐catalyzed intramolecular decarbonylative coupling of selenoesters (Scheme 1).…”
Section: Figurementioning
confidence: 99%
“…In particular, the nickel‐catalyzed decarbonylation reaction has been extensively explored by various research groups [7,8] . For instance (Scheme 1), in 2018, Szostak's research group reported the use of air and moisture‐stable nickel precatalysts to convert thioesters into thioethers by decarbonylation [9] . In the same year, Rueping's research group disclosed a new and selective cross‐coupling reaction of esters and amides with mercaptans as coupling partners [10] .…”
Section: Introductionmentioning
confidence: 99%